Strategic Management for Enhancing Employment of Vocational High School Graduates in The World of Business, Industry and Work - Dami, Zummy Anselmus; Lamijan, Lamijan; Waluwandja, Petrisia Anas; Pellokila, Ireni Irnawati; Anabokay, Yanrini Martha (JURNAL AL-TANZIM, 2024)
The effectiveness of industry involvement in vocational secondary schools can increase the absorption of vocational high school graduates in the world of work. Previous research focuses on program evaluation or industrial needs analysis, while this research focused on industrial classroom management strategies in increasing the absorption of vocational high school graduates. This study aimed to analyse strategic management's role in increasing the absorption of vocational high school graduates in the world of business, industry and work. This research uses qualitative methods with a case study type. Data collection techniques used are observation and in-depth interviews, and the analysis technique adopted in the study is pattern matching. The results found four main themes, which include: 1). vision and mission of the industrial class, 2). policies, regulations, and policies in the industrial class in increasing graduate absorption, 3). Learning programs and activities in industrial classes in increasing graduate absorption, and 4) strategic steps taken by schools in industrial class programs in increasing graduate absorption.